Genetic susceptibility loci of idiopathic interstitial pneumonia do not represent risk for systemic sclerosis: a case control study in Caucasian patients. Issue 1 (December 2016) - Wu, Minghua; Assassi, Shervin; Salazar, Gloria; Pedroza, Claudia; Gorlova, Olga; Chen, Wei; Charles, Julio; Taing, Miranda; Liao, Kelley; Wigley, Fredrick; Hummers, Laura; Shah, Ami; et al.
Abstract Background Systemic sclerosis (SSc)-related interstitial lung disease (ILD) has phenotypic similarities to lung involvement in idiopathic interstitial pneumonia (IIP). We aimed to assess whether genetic susceptibility loci recently identified in the large IIP genome-wide association studies (GWASs) were also risk loci for SSc overall or severity of ILD in SSc. Methods A total of 2571 SSc patients and 4500 healthy controls were investigated from the US discovery GWAS and additional US replication cohorts. Thirteen IIP-related selected single nucleotide polymorphisms (SNPs) were genotyped and analyzed for their association with SSc. Results We found an association of SSc with the SNP rs6793295 in theLRRC34 gene (OR = 1.14, CI 95 % 1.03 to 1.25, p value = 0.009) and rs11191865 in theOBFC1 gene (OR = 1.09, CI 95 % 1.00 to 1.19, p value = 0.043) in the discovery cohort. Additionally, rs7934606 inMUC2 (OR = 1.24, CI 95 % 1.01 to 1.52, p value = 0.037) was associated with SSc-ILD defined by imaging. However, these associations failed to replicate in the validation cohort. Furthermore, SNPs rs2076295 inDSP (β = -2.29, CI 95 % -3.85 to -0.74, p value = 0.004) rs17690703 inSPPL2C (β = 2.04, CI 95 % 0.21 to 3.88, p value = 0.029) and rs1981997 inMAPT (β = 2.26, CI 95 % 0.35 to 4.17, p value = 0.02) were associated with percent predicted forced vital capacity (FVC%) even after adjusting for the anti-topoisomerase (ATA)-positive subset. However, these associations also did not replicate in the validation cohort. Conclusions Our results add new evidence that SSc and SSc-related ILD are genetically distinct from IIP, although they share phenotypic similarities.